Adaptive security protocol for financial management networks in multi-server environments - Hu, Jie; Kang, Xuan (Frontiers in Physics, 2025)
Driven by the digital wave, the security and efficiency of financial management networks are key factors determining the competitiveness and sustainable development of enterprises. Faced with complex and ever-changing network threats in multi-server environments, traditional static security strategies are no longer sufficient to meet the security needs of modern enterprises. It is particularly important to develop a security protocol that can adapt to environmental changes and defend against potential threats. Therefore, we propose a lightweight adaptive security protocol for financial management networks in multi-server environments. This protocol uses a hash function to negotiate session keys at low computation and communication overhead, effectively protecting the transmission security of confidential messages. In addition, informal and formal analysis proves that this protocol has high security and can resist various network attack methods. We demonstrate the efficiency of the protocol in practical applications through performance comparisons. It not only has low communication overhead and good computational efficiency but also achieves lightweight message transmission, making it easy to deploy and use in multi-server environments.